Inverse and indirect mappings in embodied AI systems in everyday environments - Riaz, Maham; Erdem, Çağrı; Jensenius, Alexander Refsum (Frontiers in Computer Science, 2026)
This paper explores how musicking technologies—interactive systems with musical properties—can enhance everyday public environments. We are particularly interested in investigating the effects of musical interactions in non-musical settings, such as offices, meeting rooms, and social work areas. Traditional music technologies (such as instruments) are built for goal-directed, conscious, and voluntary interactions. We propose a new perspective on embodied AI through systems that utilize indirect, inverse, unconscious, and, at times, involuntary interactions. Four different sound/music systems are examined and discussed with regard to their activity level: a reactive “birdbox,” a reactive painting, active self-playing guitars, and interactive music balls. All these systems are multimodal, containing sensors that detect various physical inputs to produce sound and light, and having varying levels of perceived agency. The paper explores differences between direct/indirect and regular/inverse embodied AI paradigms. This study demonstrates how minimalistic interactions have the potential to yield complex and engaging musicking experiences, challenging the norms of overly intricate AI implementations.